3(c-2)=22(c-6)

Simple and best practice solution for 3(c-2)=22(c-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(c-2)=22(c-6) equation:



3(c-2)=22(c-6)
We move all terms to the left:
3(c-2)-(22(c-6))=0
We multiply parentheses
3c-(22(c-6))-6=0
We calculate terms in parentheses: -(22(c-6)), so:
22(c-6)
We multiply parentheses
22c-132
Back to the equation:
-(22c-132)
We get rid of parentheses
3c-22c+132-6=0
We add all the numbers together, and all the variables
-19c+126=0
We move all terms containing c to the left, all other terms to the right
-19c=-126
c=-126/-19
c=6+12/19

See similar equations:

| x-21+x+81=180 | | 7z−5=3+5z+6 | | 2/3+y−1/9=7 | | P=15+.5d | | -5y+5=-6y | | 3(3-x)=11 | | 8+4y=5y | | 17a+-14a+8=11 | | (2x-3)|3=1x+1/4 | | c=7c-7 | | -1+6x=-1x+12 | | x-21=x+81 | | -2p=-9−p | | 7c-7=7c+33 | | 6.2+y=13.75 | | 8y-y=9 | | 4x-36=8x-12 | | 6u=5u+5 | | 2w-19=3w-40 | | 11=3(3–x) | | 16x-20=20x-10 | | 2/3x+1/2=x-3 | | c-41=4 | | 3u+2+2u=7u-1+9 | | 3+38+9x+28=90 | | 9z+4z-12z+2=16 | | 5x+100=15x+10 | | 11=-s+4 | | 6x+5{x-2}=122 | | x+2.6=-4.6 | | 6/7=b/7 | | 9x-14=19x+4 |

Equations solver categories